2022
DOI: 10.2147/ijgm.s347163
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PDCD1 and PDCD1LG2 as Prognostic Biomarkers and Associated with Immune Infiltration in Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma has been identified to be among the most prevalent malignancies in the world and has an unfavorable prognosis. Immune checkpoints perform an essential function in many biological processes and are associated with the survival of cancer patients. The function of immune checkpoints remains unknown. Methods: We used bioinformatic methods to examine the prognostic value of immune checkpoints and the corresponding link to immune infiltration in HCC. qRT-PCR was used to validate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Disappointedly, emerging ICI immunotherapy has been shown to significantly improve clinical outcomes in HCC, but its objective response rate as monotherapy for HCC is only 15%–20% ( Ruf et al, 2021 ). Previous studies have shown that highly expressed PDCD1 has better OS and has a favorable relationship with CD8+ T cells, B cells, macrophages, CD4+ T cells ( Li et al, 2022 ). T cell immunoglobulin and ITIM domain protein (TIGIT) is a type I transmembrane protein, mainly expressed in activated T cells, Treg, memory T cells and NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Disappointedly, emerging ICI immunotherapy has been shown to significantly improve clinical outcomes in HCC, but its objective response rate as monotherapy for HCC is only 15%–20% ( Ruf et al, 2021 ). Previous studies have shown that highly expressed PDCD1 has better OS and has a favorable relationship with CD8+ T cells, B cells, macrophages, CD4+ T cells ( Li et al, 2022 ). T cell immunoglobulin and ITIM domain protein (TIGIT) is a type I transmembrane protein, mainly expressed in activated T cells, Treg, memory T cells and NK cells.…”
Section: Discussionmentioning
confidence: 99%